2006
DOI: 10.1007/s00221-006-0503-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased cannabinoid receptor density in the posterior cingulate cortex in schizophrenia

Abstract: The posterior cingulate cortex (PCC) has recently been implicated in the pathophysiology of schizophrenia, through both animal and human studies. We have recently shown abnormal glutamate, GABA, and muscarinic receptor binding in the PCC in schizophrenia. In addition, there is evidence for an abnormal endogenous cannabinoid system in schizophrenia. The endogenous cannabinoid system, including CB1 receptors, is proposed to play a role in modulating neurotransmission via affecting the release of a variety of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 165 publications
(107 citation statements)
references
References 28 publications
5
99
2
1
Order By: Relevance
“…Increased cannabinoid CB1 receptor density in the dorsolateral prefrontal, anterior and posterior cingulate cortex supported this postulation [11][12][13] . The STG is involved in the pathology of schizophrenia, particularly in auditory hallucination [14,[22][23][24] .…”
Section: Subjectsmentioning
confidence: 64%
See 2 more Smart Citations
“…Increased cannabinoid CB1 receptor density in the dorsolateral prefrontal, anterior and posterior cingulate cortex supported this postulation [11][12][13] . The STG is involved in the pathology of schizophrenia, particularly in auditory hallucination [14,[22][23][24] .…”
Section: Subjectsmentioning
confidence: 64%
“…2B) binding showed a homogeneous labelling through all cortical layers of the STG [12,15] . Even though the two ligands showed different binding patterns in the cortex, previous studies have shown that both of them are suitable to reveal the alteration of CB1 receptor density in schizophrenia [11][12][13] . A previous study in our laboratory identified an increase in the binding density of [ 3 H]SR141716A in the anterior cingulate cortex of schizophrenia patients [12] , utilising tissue mostly obtained from subjects used in the present study (all 8 schizophrenia patients and 7 of 8 control cases).…”
Section: Subjectsmentioning
confidence: 98%
See 1 more Smart Citation
“…Brains were immediately removed, frozen in liquid nitrogen and stored at -80°C. Three sites of the brain (the PFC, Cg, and hippocampus) involved in the pathophysiology of schizophrenia and antipsychotic therapeutics (Ginovart and Kapur, 2012;Lewis and Gonzalez-Burgos, 2006;Newell et al, 2006;Newell et al, 2005;Volk et al, 2010) were dissected to detect NRG1 and ErbB4 protein expression. In addition, abnormal expression of NRG1 and ErbB4 has been identified in the PFC and hippocampus of schizophrenia patients (Chong et al, 2008;Law et al, 2006).…”
Section: Western Blottingmentioning
confidence: 99%
“…Therefore, although the results from post-mortem studies are not completely consistent, evidence from the majority of studies implied an elevation in NRG1-ErbB4 signalling in schizophrenia (Hahn, 2011;Pan et al, 2011). In addition, the cingulate cortex (Cg) is also involved in the pathophysiology of schizophrenia (Natesan et al, 2006;Newell et al, 2006;Newell et al, 2005). A recent animal study indicated that mutation in the NRG1 transmembrane domain altered the expression of glutamatergic receptors in the Cg .…”
Section: Introductionmentioning
confidence: 99%